Efficient extraction and utilization of Litchi (Litchi sinensis Sonn.) fruit. - Ismail, Amin; Prasad, K. Nagendra; Asraf, Muhammad; Yueming, Jiang (Apple Academic Press Inc., 2012)
The chapter describes the efficientcy of various methods in utilising licthi fruits.